1985
DOI: 10.1037/0021-843x.94.3.308
|View full text |Cite
|
Sign up to set email alerts
|

Depressive self-schemas, life stress, and vulnerability to depression.

Abstract: A vulnerability model of depression was tested by hypothesizing that depressogenic self-schemas that interact with schema-congruent negative life events will be associated with depression. Ninety-three college students were followed prospectively for four monthly assessments of both interview-and questionnaire-measured stressful life events, and clinical interview-and questionnaire-measured depression. An information-processing schema model of vulnerability was used to define subgroups of 46 dependent and 32 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
251
0
3

Year Published

1988
1988
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(276 citation statements)
references
References 28 publications
22
251
0
3
Order By: Relevance
“…Attentional and mnemonic biases toward processing of mood-congruent information including sad, unpleasant and negative words, emotional facial expressions, and memories also are reliable and relatively specific neuropsychological findings of MDD (Watkins et al, 1996;Murphy et al, 1999), and have been found in remitted depressed subjects suggesting some state-independence (Hammen et al, 1985;Koschack et al, 2003). Experimental depletion of central serotonin led to the emergence of mood-congruent memory bias , and physiological activation of the brain regions that have been found to be involved in mood-congruent information processing (Elliott et al, 2002) is thought to play a key role in MDD (Drevets et al, 1997), thus implicating good biological validity.…”
Section: Depressed Mood (Mood Bias Toward Negative Emotions)mentioning
confidence: 96%
“…Attentional and mnemonic biases toward processing of mood-congruent information including sad, unpleasant and negative words, emotional facial expressions, and memories also are reliable and relatively specific neuropsychological findings of MDD (Watkins et al, 1996;Murphy et al, 1999), and have been found in remitted depressed subjects suggesting some state-independence (Hammen et al, 1985;Koschack et al, 2003). Experimental depletion of central serotonin led to the emergence of mood-congruent memory bias , and physiological activation of the brain regions that have been found to be involved in mood-congruent information processing (Elliott et al, 2002) is thought to play a key role in MDD (Drevets et al, 1997), thus implicating good biological validity.…”
Section: Depressed Mood (Mood Bias Toward Negative Emotions)mentioning
confidence: 96%
“…Probes for episodic stressful life events were embedded in the chronic stress interview (e.g., Hammen, 1991;Hammen, Marks, Mayol, & deMayo, 1985), modeled after the contextual threat assessment of stressful life events (Brown & Harris, 1978). In contrast to chronic stress, episodic stress included discrete life events with a discernable beginning and ending.…”
Section: Methodsmentioning
confidence: 99%
“…These three items were part of the Life Events Scale, a multiitem battery that asks respondents to indicate (1 = yes or 0 = no) whether events in several areas of day-to-day living, including sexuality, had occurred in the past year (Hammen, Marks, De Mayo, & De Mayo, 1985). On this scale, definitions of affair and sexual problems are left up to the respondents themselves.…”
Section: Sexualitymentioning
confidence: 99%